CFD Analysis of the Effect of Heat Distribution on Different Heating Pad Piping Arrangements for Flexitank Application - Saiful Azam, Syafiqah Ruqaiyah; Darlis, Nofrizalidris; Mustaffa, Norrizal; Rahman Azahar, Mohamad Amirur; Sadun, Amirul Syafiq; Abu Hassan, Omar; Taib, Ishkrizat; Mustaffa, Khairul Nizam; Hashim, Muhamad Mohshein (semarak ilmu, 2023)
Variations in piping arrangements of heating pad for flexitank applications causes a difference in the time required to completely liquidise the liquid during the discharging process. As reference, a conventional heating pad took about 48 hours to heat up the flexitank. There are many commercials heating pad used in flexitank applications to facilitate the discharging process of liquid. However, there are still uncertainty or limitation reference regarding the heating pad for flexitank application. One of the solutions to minimize the time taken for discharging processis identify the finest piping arrangement of heating pad. Based on the previous study, piping arrangement plays an important role for performance of the heating pad heat distribution. Thus, this paper aims to study the thermal behaviour of different heating pad arrangement for flexitank application with references to commercial arrangement of floor heating pad based on various inlet pressure using computational fluid dynamics (CFD) simulation software. This study was done by comparing thermal analysis of three piping arrangement which is conventional arrangement, Serpentine arrangement, and Spiral arrangement. The geometry of heating pad was created using Computer-Aided Design (CAD) software, SolidWorks. The results have discussed some important components parameter that must be controlled for the system to function efficiently. These parameters include pressure distribution within the pipes, temperature distribution along the pipes, and piping arrangement patterns. The simulation results show that the Counterflow arrangement has a uniform temperature distribution between the inlet and outlet. The study concluded that counterflow arrangement generally the best arrangement among these three since the configuration allowing less pressure losses and better thermal distribution on flexitank and heating pad. This study is therefore useful for designers to explore more adequately the benefits of underfloor heating system on many applications.